Decrease of hospitalizations and length of hospital stay in patients with schizophrenia spectrum disorders treated in a community mental health service in rural Greece. (November 2020) - Peritogiannis, Vaios; Gioti, Panagiota; Gogou, Afroditi; Samakouri, Maria
Background: The treatment of severe and chronic mental disorders, such as schizophrenia and related syndromes, is largely based on community mental health services. Aims: The objective of the present study was to assess hospital admissions and length of hospital stay in patients with schizophrenia and related disorders, who are engaged to treatment with a Mobile Mental Health Unit (MMHU I-T) in a defined rural catchment area in Greece. Method: Data were retrieved retrospectively for 76 patients with schizophrenia and related disorders. For each patient, comparison was made for the same interval prior and after engagement to treatment with the MMHU I-T. Results: The average age of patients was 56 years and the mean illness duration was 28 years. The mean follow-up duration was 5.3 years. There was a statistically significant decrease in the annual average of the number of voluntary and involuntary hospitalizations and on days of hospital stay after treatment engagement with the MMHU I-T. Conclusions: Treatment of schizophrenia spectrum disorders in rural residents by the MMHUs may contribute to the reduction of patients' admissions and length of hospital stay. Future research should address the cost-effectiveness of such interventions.